Caring for sick people in advanced phases of a disease - de Moraes, Tania Mara (O Mundo da Saúde, 2009)
Even though there are currently many technological advances, still we have a great number of diseases for which, even after the efforts carried through for combating, there is a moment where cure is not possible anymore. This causes discomfort not only for patients and their relatives but also for the caring team. This study is a bibliographical survey covering the period 1992-2008 aiming to improve knowledge on taking care of a patient in advanced phases of a disease, as well as on support for patients’ relatives. Many changes occur in the life of a patient from the moment a diagnosis of a non curable disease is done. As health professionals, we need to be able to care for them considering physical, psycho-affective and spiritual necessities, according to ethical standards. We need to understand what occurs with this patient and her family, respecting them and seeking to care for their real necessities, contributing for them to improve their quality of life, notwithstanding the life time remaining so that they have a death with dignity.